2017
DOI: 10.1111/vsu.12652
|View full text |Cite
|
Sign up to set email alerts
|

Canine cranial cruciate ligament deficient stifle biomechanics associated with extra‐articular stabilization predicted using a computer model

Abstract: Our computer model predicted controlled tibial translation, decreased cruciate and collateral ligament loads, and a change in femorotibial rotation from internal to external with LFTS and TR stifle management as compared to the CrCL-deficient stifle. This study demonstrates how computer modeling can be used to evaluate biomechanics of stifle stabilization surgical techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…2,3 Numerous surgical treatment options have been proposed and have been grouped by extra-capsular, intra-articular or osteotomy techniques. 4 Lateral fabellotibial suture is an extra-capsular technique first described in 1970. 5 A heavy non-absorbable suture material is placed around the sesamoid of the lateral head of the gastrocnemius tendon and through bone tunnel(s) made in the tibial tuberosity mimicking craniocaudal restraint of the cranial cruciate ligament.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Numerous surgical treatment options have been proposed and have been grouped by extra-capsular, intra-articular or osteotomy techniques. 4 Lateral fabellotibial suture is an extra-capsular technique first described in 1970. 5 A heavy non-absorbable suture material is placed around the sesamoid of the lateral head of the gastrocnemius tendon and through bone tunnel(s) made in the tibial tuberosity mimicking craniocaudal restraint of the cranial cruciate ligament.…”
Section: Introductionmentioning
confidence: 99%
“…Outcome evaluations of surgical treatments for CCLD have been conducted by retrospective studies ( 26 ), in vivo limb function evaluation with force plates ( 20 ), arthroscopy ( 24 , 27 , 28 ), osteoarthritis scoring ( 27 , 28 ), computer model prediction ( 29 ), and ex vivo biomechanical studies ( 30 , 31 ). Among these methods, ex vivo biomechanical testing allows for direct experimental exploration of the effects of diseases or therapeutic factors on stifle kinematic responses.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13] The biomechanical properties of these 2 techniques used for stifle joint stabilization, with both osteotomies and extracapsular fixation, have been widely evaluated in dogs. [14][15][16][17][18][19][20][21] Nevertheless, there are limited reports available that assess the biomechanical behavior of extracapsular techniques for stifle stabilization in cats. 7,[22][23][24] A biomechanical study 7 on cat cadaveric stifle joints demonstrated that a lateral femoro-tibial suture with the screw placed at the quasi-isometric point provides better stabilization to the joint in the proximal-distal plane compared to a standard lateral suture.…”
mentioning
confidence: 99%